Developmental and Biographical Issues in Radicalization Pathways: A Comparative Case Analysis of Homegrown German Convicts of Islamist Terrorism-Related Offenses - Moeller, Mika Josephine (Terrorism and political violence, 2024)
In this paper, developmental and biographical issues in individual biographical pathways of radicalization are examined from birth through to conviction for Islamist terrorism-related offenses. The source of data was court files of forty-five homegrown Germans convicted of Islamist terrorism-related offenses (age range at the time of the crime: 15 to 38; mean: 24 years, SD: 5; four female convicts). Using coding and constant case comparison techniques, a multiple comparative case analysis was conducted. This article gives an account of what individuals who were later convicted of Islamist terrorism-related offenses experienced in their life course and when. Patterns of relations between the biographical experiences and developmental psychological phases are identified, visually represented, and measured using odds ratios. In particular, the importance of the distinction between the developmental psychological phases of adolescence, emerging adulthood, and adulthood is emphasized and its meaning for radicalization processes is discussed. The interplay of cumulative vulnerabilities and developmental psychological phases are discussed. Guidance is provided on which topics are best addressed in prevention interventions and at what times.